Visually evoked potentials (VEPs) across the visual field in hearing and deaf cats - Mitzelfelt, Thomas; Bao, Xiaohan; Barnes, Paisley; Lomber, Stephen G. (Frontiers in Neuroscience, 2023)
Congenitally deaf cats perform better on visual localization tasks than hearing cats, and this advantage has been attributed to the posterior auditory field. Successful visual localization requires both visual processing of the target and timely generation of an action to approach the target. Activation of auditory cortex in deaf subjects during visual localization in the peripheral visual field can occur either via bottom-up stimulus-driven and/or top-down goal-directed pathways. In this study, we recorded visually evoked potentials (VEPs) in response to a reversing checkerboard stimulus presented in the hemifield contralateral to the recorded hemisphere in both hearing and deaf cats under light anesthesia. Although VEP amplitudes and latencies were systematically modulated by stimulus eccentricity, we found little evidence of changes in VEP in deaf cats that can explain their behavioral advantage. A statistical trend was observed, showing larger peak amplitudes and shorter peak latencies in deaf subjects for stimuli in the near- and mid-peripheral field. Additionally, latency of the P2 wave component had a larger inter-sweep variation in deaf subjects. Our results suggested that cross-modal plasticity following deafness does not play a major part in cortical processing of the peripheral visual field when the “vision for action” system is not recruited.